The development of e-commerce in the grocery retail sector during and after the COVID-19 pandemic - Drymlová, Michaela; Šaroch, Stanislav, 1970-; Horáková, Ludmila; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The COVID-19 pandemic has had a significant impact on retail, with online grocery sales experiencing rapid growth. Increased demand for online shopping, changing consumer preferences and retailers adapting to new logistical challenges have had a long-term impact on the entire market. The aim of this bachelor thesis is to assess the long-term impact of the COVID-19 pandemic on online grocery retailers in the Czech market, with a particular focus on Rohlík.cz. The thesis provides an in-depth understanding of how the pandemic affects customer behaviour, logistics and innovation strategies in online food sales. The theoretical part focuses on the area of e-commerce, the evolution of food retailing and the impact of the COVID-19 pandemic on this market segment. The practical part analyses the company Rohlík.cz - its operation before the pandemic, changes in demand during the pandemic, impact on logistics processes and innovations introduced. Finally, the paper compares selected indicators with the British company Ocado Retail, which shows similar features to Rohlík.cz.
Vedoucí práce: Stanislav Šaroch
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses